Struktur Komunitas Vegetasi Pada Blok Perlindungan di Kawasan Taman Hutan Raya Lapak Jaru Kabupaten Gunung Mas: Vegetation Community Structure in Protection Block in The Lapak Jaru Highway Forest Park Area Gunung Mas District - Setiarno, Setiarno; Sopya, Sopya; Tanduh, Yusinta; Junaedi, Ajun; Yulianti, Reri (HUTAN TROPIKA, 2024)
Botanical Forest Park (Tahura) is very important to support human life and the environment. The purpose of the study was to analyze the structure of the vegetation community, including the level of diversity, and the similarity of the vegetation community. The research method follows the sampling technique procedure with the plot method. Data were analyzed using the Index of Important Value to test the mastery of the species, the Shannon-Wiener Index to test the level of diversity of vegetation species, and community stability, community similarity index to test the similarity between flora communities. The results obtained are the value of the species diversity index, in general, is included in the medium category, which means that productivity is sufficient, ecosystem conditions are quite balanced, and ecological pressure is moderate. The species evenness index is high, the species richness index is in the medium category, and the similarity index between plant communities is very high.